Critical success factors research based on the whole process practice of Guangxi Laibin B electricity power plant bot project - FENG, Liujiang (Institutional Knowledge at Singapore Management University, 2021)
Given the lack of research on the critical success factors of the whole process of BOT projects, this paper conducts research on the BOT projects in Fujian Meizhou Bay, Guangdong Shajiao, and Guangxi Laibin, which applies the critical success factor (CSF) model analysis, and uses scientific questionnaire scoring evaluation to determine the success or failure of the BOT projects. The research results of the paper are in line with the local governments’ summaries and evaluation of the power plants after the end of the projects. This paper uses a mixed research method combining "expert argument + questionnaire + case analysis" to summarize the critical factors for the success of BOT projects. The critical factors are extracted from five dimensions: "economic development needs”, “social environmental support”, “technology and funding guarantee”, “consideration of all parties’ interests” and “scientific project management". The specific influencing factors, "economic development level and capital demand", "credit guarantee", "technical and business plan and financing plan", "detailed project plan and development", "risk sharing mechanism" play a positive role in promoting and decisive influence on the smooth implementation of the project. This paper takes the Laibin B power factory BOT project as a typical case, combined with the entire process of start-up, construction, operation, and handover, and deeply analyzes the critical factors for the success of the whole process of the project. The important role of the five factors is highly consistent with the criticality of the success of the project.